Gross Motor Function Classification System Specific Growth Charts—Utility as a Risk Stratification Tool for Surgical Site Infection Following Spine Surgery. Issue 4 (April 2019) - Baranek, Eric S.; Maier, Stephen P.; Matsumoto, Hiroko; Hyman, Joshua E.; Vitale, Michael G.; Roye, David P.; Roye, Benjamin D.
Abstract : Background: There is currently minimal evidence that preoperative malnutrition increases surgical site infection (SSI) risk in children with cerebral palsy (CP) undergoing spinal deformity surgery. Growth charts specifically for patients with CP have been created to aid in the clinical interpretation of body mass index (BMI) as a marker of nutritional status, but to our knowledge these charts have never been used to risk stratify patients before orthopaedic surgery. We hypothesize that patients with CP who have BMI-for-age below the 10th percentile (BMI⩽10) on CP-specific growth charts are at increased risk of surgical site infection following spinal deformity surgery compared with patients with BMI-for-age above the 10th percentile (BMI>10). Methods: Single-center, retrospective review comparing the rate of SSI in patients with CP stratified by BMI-for-age percentiles on CP-specific growth charts who underwent spinal deformity surgery. Odds ratios with 95% confidence intervals and Pearson χ 2 tests were used to analyze the association of the measured nutritional indicators with SSI. Results: In total, 65 patients, who underwent 74 procedures, had complete follow-up data and were included in this analysis. Ten patients (15.4%) were GMFCS I-III and 55 (84.6%) were GMFCS IV-V; 39 (60%) were orally fed and 26 (40%) were tube-fed. The rate of SSI in this patient population was 13.5% with 10 SSIs reported within 90 days of surgery. There was a significant association between patients with a BMI below the 10th percentile on GMFCS-stratified growth charts and the development of SSI (OR, 13.6; 95% CI, 2.4-75.4; P =0.005). All SSIs occurred in patients that were GMFCS IV-V. There was no association between height, weight, feeding method, or pelvic instrumentation and development of SSI. Conclusions: CP-specific growth charts are useful tools for identifying patients at increased risk for SSI following spinal instrumentation procedures, whereas standard CDC growth charts are much less sensitive. There is a strong association between preoperative BMI percentile on GMFCS-stratified growth charts and SSI following spinal deformity surgery. Level of Evidence: Level III—Retrospective Study. Abstract : Supplemental Digital Content is available in the text.